Growing old in resource communities: Exploring the links among voluntarism, aging, and community development. (24th March 2014) - Skinner, Mark W.; Joseph, Alun E.; Hanlon, Neil; Halseth, Greg; Ryser, Laura
Abstract This article addresses the implications of "resource frontier aging" with a particular emphasis on understanding the role of the voluntary sector in supporting older people living in resource hinterland regions, and in sustaining economic and social development in their communities. Informed by recent calls for greater attention to the diverse experiences of rural aging, individually and collectively, and drawing on previous research on voluntarism in aging rural communities and on community development in Canada's resource hinterland, we conceptualize voluntarism as a multifaceted process that both shapes and is shaped by the interactions between older people and aging places. We articulate an approach for interrogating initiatives that link voluntarism, aging, and community development together, and present findings from an exploratory analysis of local media from two resource towns in northern British Columbia to identify and describe the interrelationship between voluntary sector activities in support of community development and those in support of aging in place. The findings provide evidence of the multiple, nuanced, and reciprocal ways in which voluntarism creates and reinforces the connections between aging and community development, often via the leadership and participation of older residents. Avenues for further research aimed at developing an in‐depth understanding of voluntarism as a potentially transformative process in resource frontier communities are discussed.